Time Course of Axon and Myelin Degeneration in Peripheral Nerves in Experimental Autoimmune Neuritis Rats. (June 2019) - Tomikawa, Emi; Mutsuga, Mayu; Hara, Kojiro; Kaneko, Chihiro; Togashi, Yuko; Miyamoto, Yohei
Experimental autoimmune neuritis (EAN) is an animal model for Guillain–Barré syndrome (GBS), which results in neurological symptoms and histopathological changes in peripheral nerves. In this model, the correlation between the progression of the disease and the histopathological changes is not clear. To further examine histopathological changes in peripheral nerves in EAN rats, sciatic nerves were sampled at onset (day 10), peak (day 16), and recovery (days 22 and 25) of neurological symptoms in P2(57-81)-peptide-administered rats. Axon and myelin degeneration was observed by light microscopy at onset, degeneration became severe at peak, and persisted at recovery. Densities of myelinated nerve fibers and myelin areas decreased from day 10 to a minimum on day 22. Slight axon and myelin degeneration, such as accumulation of vesicles in axons and focal myelin splitting and folding, was observed by transmission electron microscopy at onset; severe degeneration, such as axonal loss, myelin ovoid, and demyelination, increased at peak; and regenerative changes, such as remyelination and enlargement of Schwann cell cytoplasm, occurred at recovery. These results suggest that EAN rats have histopathological similarities to some types of GBS patients and that EAN rats are a useful model to understand the pathogenesis of GBS.